1999
DOI: 10.1007/bf02723850
|View full text |Cite
|
Sign up to set email alerts
|

Mid-arm circumference for detecting malnutrition during infancy

Abstract: Mid-arm circumference (MAC) has been extensively used at 1-5 years of age as an age-independent indicator of protein-energy malnutrition (PEM). Its role below 12 months of age has not been studied adequately and a search for a clinically reliable cut-off point has not been systematically done. This study was planned to establish the age-independent character of MAC within the 6-12 month age group and identify a cut-off point demonstrating the maximum sensitivity and specificity in detection of PEM. Two hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Our finding of a significantly decreased MUAC is in agreement with Alatrouni [17], who attributed this to muscle atrophy which is found in all types of PEM. Bhatia et al [20] also reported that the decrease in MUAC may be due to loss of subcutaneous fat which is observed in marasmus and marasmic-kwashiorkor. The mean MUAC was significantly (p<0.001) lower in the malnourished children and the differences were more marked with the increasing severity of malnutrition, though the mean weight, and BMI were similar among the different classes of PEM.…”
Section: Discussionmentioning
confidence: 96%
“…Our finding of a significantly decreased MUAC is in agreement with Alatrouni [17], who attributed this to muscle atrophy which is found in all types of PEM. Bhatia et al [20] also reported that the decrease in MUAC may be due to loss of subcutaneous fat which is observed in marasmus and marasmic-kwashiorkor. The mean MUAC was significantly (p<0.001) lower in the malnourished children and the differences were more marked with the increasing severity of malnutrition, though the mean weight, and BMI were similar among the different classes of PEM.…”
Section: Discussionmentioning
confidence: 96%
“…Prevalence of under‐weight, estimated by BMI cutt‐off points only, was higher compared with the CDC reference values. According to the classification of Waterlow and colleagues (1977) and Bhatia and colleagues (1999) for malnutrition, the non‐significant difference existed between children with underweight and children with healthy weight suggested no stunting in the underweight group. Based on the work of Collins (1996) and Ojo and colleagues (2002), we should advise, in future work, the combination of anthropometric variables (MUAC and BMI cutt‐off points) and clinical variables in the determination of prevalence of malnutrition and in the formulation of intervention strategies for nutrition rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 9% of children below 5 years of age suffer from wasting indicating malnutrition (weight-forheight below -2 standard deviations (<-2 SD) of the NCHS/WHO reference values) and are at risk of death or severe impairment of growth and psychological development. Alternatively simple anthropometric measures can be usedcommonly the mid upper arm circumference (MUAC) [7][8][9].…”
Section: Nutrition In Childrenmentioning
confidence: 99%